Design and fabrication of lead detection test rig - Mohamad Shafis, Ahmad Ramli (2013)
Manufacturing is a process of converting raw material into product. It can be described the transformation of materials into items of greater value by means of one or more processing and /or assembly operations. The study of manufacturing was very important in order to carry out this project to ensure that students understand on what are need to do. This project is about designing and fabricating of lead detection test rig. This project involves the process of designing the piping by consider the type of pipe, and the component that involve to detect the leakage in the pipelines. From the investigated, there have many methods to detect the leak. From the investigated, the design was improved and fabricates the test rig for the analysis. The analysis were run after the fabricate is completed. After all the process had been done, these clotheslines may help us to understand the fabrication and designing process that involved in this project.